Post-traumatic glioma: Report of one case and review of the literature - Zhou, Bo (Ivyspring International Publisher, 2010)
We report one case of brain glioma that developed in the scar of an old brain trauma. A 45-year-old man who presented with seizures; MRI showed a large mass in the right temporal region. Surgical biopsy showed a glioblastoma multiforme. The patient had suffered a cranial trauma in a road accident 10 years previously with an intracerebral hematoma in the right temporal region. This case fulfills the established criteria for a traumatic origin of brain tumors and adds further support to the relationship between cranial trauma and the onset of glioma. As stated by other authors, an association between head trauma and brain tumor risk cannot be ruled out and should be studied further.